Fungi of Raffaelea genus (Ascomycota: Ophiostomatales) associated to Platypus cylindrus (Coleoptera: Platypodidae) in Portugal - Lima, Arlindo (2008)
In the study of the fungi associated to Platypus cylindrus, several fungi were isolated from the insect and its galleries in cork oak, among which three species of Raffaelea. Morphological and cultural characteristics, sensitivity to cycloheximide and genetic variability had been evaluated in a set of isolates of this genus. On this basis R. ambrosiae and R. montetyi were identified and a third taxon segregated witch differs in morphological and molecular characteristics from the previous ones. In this work we present and discuss the parameters that allow the identification of specimens of the three taxa. The role that those ambrosia fungi can have in the cork oak decline is also discussed taking into account that Ophiostomatales fungi are pathogens of great importance in trees, namely in species of the genus Quercus.